?Realidad o discurso? : los derechos humanos de los migrantes centroamericanos en México - Flor Patiño, Y. Imanol de la (Serie Doctrina jurídica ;, 2014)
Systematic theoretic and legal study of extent to which human rights of immigrants from Central America crossing through Mexico are respected and protected in this country. Compares two legal instruments--Mexico's Immigration Law and International Convention on Protection of Migrant Workers and Families--and identifies conflicts, inconsistencies, and grey areas that have left room for blatant violations. Author works with legal area of Mexico's Ministry of Foreign Relations.